2006
DOI: 10.1016/j.exphem.2005.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow production of lung cells: The impact of G-CSF, cardiotoxin, graded doses of irradiation, and subpopulation phenotype

Abstract: Objective-Previous studies have demonstrated the production of various types of lung cells from marrow cells under diverse experimental conditions. Our aim was to identify some of the variables that influence conversion in the lung. Methods-In separate experiments, mice received various doses of total-body irradiation followed by transplantation with whole bone marrow or various subpopulations of marrow cells (Lin −/+ , ckit −/+ , Sca-1 −/+ ) from GFP + (C57BL/6-TgN[ACTbEGFP]1Osb) mice. Some were given intramu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
83
1
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(88 citation statements)
references
References 24 publications
2
83
1
2
Order By: Relevance
“…In a similar vein, by studying murine lung originator cells and murine target marrow cells, Aliotta et al [28][29][30] showed that lung RNA was transferred to marrow cells inducing the expression of lung-specific mRNAs (surfactants A-D, Clara cell-specific protein, and aquaporin-5) and proteins and altering the function of marrow cells toward that of pulmonary cells. This later was shown by the increase in prosurfactantpositive pulmonary cells after transplant with vesicle exposed marrow.…”
Section: Vesicle Transfer Of Rna and Target Cell Phenotype Changementioning
confidence: 99%
See 1 more Smart Citation
“…In a similar vein, by studying murine lung originator cells and murine target marrow cells, Aliotta et al [28][29][30] showed that lung RNA was transferred to marrow cells inducing the expression of lung-specific mRNAs (surfactants A-D, Clara cell-specific protein, and aquaporin-5) and proteins and altering the function of marrow cells toward that of pulmonary cells. This later was shown by the increase in prosurfactantpositive pulmonary cells after transplant with vesicle exposed marrow.…”
Section: Vesicle Transfer Of Rna and Target Cell Phenotype Changementioning
confidence: 99%
“…These meaningless criteria nevertheless hurt the field and impaired progress. In our own studies, we had demonstrated that the engraftment of GFP + marrow cells into lethally irradiated mice resulted in the appearance of GFP + pulmonary epithelial cells in the lungs of transplanted mice [28]. Subsequent studies showed that when lung tissue was cultured opposite murine marrow cells, but separated from them by a cell impermeable 0.4 mm membrane, the marrow cells expressed the pulmonary-specific mRNAs, surfactants A-D, aquaporin-5, and Clara cellspecific protein [29].…”
Section: Providence Experiencementioning
confidence: 99%
“…17 The administration of radiolabeled, trackable hematopoietic stem cells results in initial transient homing of these cells to the lung, then a secondary clearance from the lung, and migration to bone marrow sites. 24 Furthermore, initial lodging of engrafted hematopoietic cells to reticular/adventitial cell sites in the marrow sinuses is followed by secondary migration to sites of the true hematopoietic stem cell niche. 17 Increased mobilization of hematopoietic cells from the marrow into the circulation is known to increase following G-CSF, keratinocyte growth factor (KGF) or IL-11 administration.…”
Section: Gene Therapy Stem Cell Protection Js Greenbergermentioning
confidence: 99%
“…12,[24][25][26] Toxicity to the non-hematopoietic organ microenvironment can facilitate engraftment or repopulation by cells from other organs including the marrow. 24,27,28 Exposure of the rat liver to carbon tetrachloride, followed by further damage to repopulating cells by 3-amino-fluorine alters the liver microenvironment to accept bone marrow-derived cells which are capable of differentiating into both hepatocytes and hepatic duct cells. 27 Irradiation and/or chemical injury to the stromal microenvironment of the heart, lung, esophagus and central nervous system also facilitates homing and differentiation of bone marrow-derived cells into functioning components of that organ.…”
mentioning
confidence: 99%
See 1 more Smart Citation